2020
DOI: 10.1002/jhbp.863
|View full text |Cite
|
Sign up to set email alerts
|

Salvage living donor liver transplantation for hepatocellular carcinoma recurrence after hepatectomy: Quantitative prediction using ADV score

Abstract: Background: Salvage liver transplantation is a definite treatment for recurrent hepatocellular carcinoma (HCC) after hepatectomy. ADV score is calculated by multiplying α-fetoprotein and des-γ-carboxyprothrombin concentrations and tumor volume.Prognostic accuracy of ADV score was assessed in patients undergoing salvage living donor liver transplantation (LDLT) and their outcomes were compared with patients undergoing primary LDLT. Methods: This study was a retrospective, single-center, case-controlled study.Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…However, the treatment response for post-resection tumor recurrence was not taken into account in the analysis; thus, further validation studies were necessary. Early tumor recurrence after liver resection was not a significant risk factor for posttransplant tumor recurrence in a recent high-volume study [23].…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…However, the treatment response for post-resection tumor recurrence was not taken into account in the analysis; thus, further validation studies were necessary. Early tumor recurrence after liver resection was not a significant risk factor for posttransplant tumor recurrence in a recent high-volume study [23].…”
mentioning
confidence: 79%
“…However, various treatment responses for post-resection tumor recurrence were not taken into account; thus, further validation study was necessary. A recent high-volume single-institution study demonstrated that early tumor recurrence after liver resection was not a significant risk factor for posttransplant tumor recurrence, in which a 2-factor prognostic prediction model with the Milan criteria and the ADV score at a cutoff of 4 log was proposed [23].…”
Section: Discussionmentioning
confidence: 99%
“…The large-caliber synthetic vascular graft contains multiple vertical pleats which can be stretched, suggesting the need to avoid redundancy through application of adequate tension [6,7]. The indications of LDLT for HCC have been expanded beyond the Milan criteria [8][9][10][11]. A few reports revealed higher rates of posttransplant HCC recurrence following LDLT than DDLT [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The ADV score is a surrogate biomarker for posttransplant prognosis in both salvage and primary LDLT recipients. Prognostic models incorporating ADV scores can help determine whether to perform salvage LDLT [23].…”
Section: Quantitative Prognostic Prediction Using Adv Score In Asan Medical Center (2020) [23]mentioning
confidence: 99%